Controlling the p-type conductivity of SnO by doping with nitrogen and hydrogen - Becker, M.; Hamann, R.; Hartung, D.; Voget-Grote, C.; Graubner, S.; Hoffmann, P.; Ronning, Carsten; Polity, A.; Klar, P. J. (Journal of Applied Physics, 2019)
Two series of SnO thin films, one doped with N and one doped with H, were deposited on c-plane sapphire by reactive ion beam sputter deposition starting from growth parameters optimized for stoichiometric SnO. The amounts of dopants incorporated into the SnO:H and SnO:N samples were quantified by secondary ion mass spectroscopy. The influence on the structural and electrical properties of SnO thin films was studied as a function of dopant concentration. In the case of N doping, all N incorporated, probably as N O, are active as the acceptor and exhibit long-term stability. We assign an acceptor activation energy of 100 to 150 meV to N O. However, we observe a change in the film morphology at a critical N concentration of about 7 ⋅ 10 17 cm − 3, which deteriorates the structural properties of the films. In the case of SnO:H, the situation is different. We observe an outdiffusion of H after growth, i.e., the samples are not stable in the long term. Nevertheless, all H incorporated up to a H-content of 10 19 cm − 3 seem to be electrically active and exhibit an activation energy between 150 and 250 meV, likely corresponding to H i. Furthermore, at H contents above 10 19 cm − 3, we observe molecular H 2 inside the SnO:H thin films. We conclude that N doping of SnO is better suited for tuning the p-type conductivity of SnO. However, it will be essential to overcome the morphology change observed at the critical N concentration to fully explore the tunability of the p-type conductivity in device applications.
CRIS-Team Scopus Importer:2023-04-20